Design and pitfalls of Basel's new liquidity rules - Philipp König; David Pothier (DIW Economic Bulletin, 2016)
Following the financial crisis of 2008/09, the Basel Committee on Banking Supervision introduced a new framework for banking regulation, commonly known as Basel III. For the first time since the inception of global banking regulation in 1988, Basel III contains explicit mandatory rules for liquidity regulation. The cornerstones of the new liquidity regulation are two balance sheet ratios that seek to reduce banks' liquidity transformation. While regulation addressing liquidity risk in the banking sector is clearly desirable, the new rules have several pitfalls. First, the two ratios rely on different definitions of liquidity and funding stability which makes the regulatory framework unnecessarily complicated and opaque. Second, it is unclear whether a ratio-based approach is the most effective and efficient way to rectify liquidity problems in the banking sector. Third, it is unclear how the new liquidity rules interact with existing monetary implementation frameworks of central banks and whether they hamper a smooth steering of policy interest rates.
Keywords: G2; G21; G28; 330; liquidity regulation; Basel III; financial intermediation